Sports Stories - Durant Alan; Kearney David (London Kingfisher Publications, 2000)
This collection of stories is aimed at young sports enthusiasts. It includes over 20 stories covering a wide variety of international sports from soccer and horse riding to go-karting and swimming.
Keywords: English Literature